Gamification in Inclusive Education for Children with Disabilities: Global Trends and Approaches - A Bibliometric Review - Jadán-Guerrero, Janio (2023)
Given the growing attention to the intersection between technology and education, gamification has emerged as a strategy with great benefits. This bibliometric review addresses gamification’s current and future relevance in the educational field, focusing on its use as a pedagogical strategy to improve the learning and engagement of children with disabilities. Sixty-six studies published between 2001 and 2023 were analyzed, evaluating the most influential articles, main keywords, prominent authors, collaborating institutions, and funding sources. The literature suggests that gamification offers inclusive and personalized learning opportunities covering various disabilities. Methodologies and approaches to implement gamification were identified, including game elements, user-centered design techniques, and emerging technologies such as virtual reality, artificial intelligence, and educational robotics. However, challenges and areas for improvement were also found, such as the need for more long-term empirical evidence and the importance of considering individual differences and specific needs when designing gamification strategies. The review highlights the importance of strengthening collaborative networks between researchers and education professionals to disseminate best practices and promote more effective gamification approaches adapted to the needs of children with disabilities. Collaboration between educators, game developers, researchers, and parents are crucial to ensure that gamification efforts are inclusive and meet the diverse needs of students.